C.04 Dynamic MRI in the evaluation of the craniocervical junction of pediatric down syndrome patients. (2nd June 2017) - Tu, A; Melamed, E; Krieger, M
Abstract : Background: Down syndrome is the most common inherited disorder. Some patients develop craniocervical instability. Existing screening guidelines were developed prior to direct imaging of the neuraxis. We present parameters for potential instability using dynamic MRI of the craniocervical junction.Methods: A retrospective review from 2001 – 2015 was carried out. Patients were symptomatic if they had myelopathy or signal changes at the craniocervical junction. Radiographic measurements were taken. Data analysis was performed with SPSS.Results: 36 patients were included. Symptomatic patients had smaller CCD (9.4 mm vs 13.8 mm; p=0.003) and greater ADI (4.4mm vs 3.0 mm; p=0.01) on resting MRI . During dynamic imaging, symptomatic patients had greater changes in CCD (5.2 vs 2.7 mm; p <0.001) and ADI (2.8 vs 1.3 mm; p=0.04). These patients were also more likely to have a bony anomaly (0.5 vs 0.13; p=0.03).Conclusions: This study identifies parameters that can be used to distinguish unstable patients. A CCD of less than 5 mm or ADI greater than 4.4 mm on static MRI; change greater than 3 mm in ADI or 5mm on CCD during dynamic MRI; or any bony abnormality warrants further investigation. Asymptomatic patients should be followed although most do not progress.